Going GAGAS for due process: examining Yellow Book standard participation. Issue 2 (6th May 2020) - Flasher, Renee; Lau, Michelle; Marshall, Dara M.
Abstract : Purpose: The US federal government requires auditors to follow governmental auditing standards when performing audits of entities expending significant federal government dollars. This study explores stakeholder participation during the comment letter phase of government auditing standard setting to determine if participation is symbolic or substantive. Design/methodology/approach: Researchers conduct an analysis of the 179 comment letters submitted to the US Government Accountability Office (GAO) and received for their 2010 and 2017 exposure drafts of government auditing standards. Findings: The distribution of stakeholder participation groups in the government auditing standard-setting process differs from the distribution in the private company auditing standard-setting process. On average, participants submit letters that are greater than two pages in length. Participants also contribute feedback on topics that the GAO directly solicits. Taken together, the results demonstrate stakeholder behaviors that are consistent with a substantive rather than symbolic due process involvement for government auditing standards. Research limitations/implications: Stakeholder beliefs are inferred based on the observed behavior of comment letter submissions. Also, there is a subjective element to the classification of the comment letters for the study. Practical Implications: Given the far-reaching implications of Yellow Book auditing standards on public, private and nonprofit entities, the findings are relevant to a heterogeneous audience. This study reveals opportunities for users of government auditing standards, practitioners and academics for greater involvement in due process standard setting to bring additional legitimacy to the GAO and its standard-setting activities. Originality/value: Beyond the current study, little empirical research examines Yellow Book auditing standards or the due process through which these standards are established. This is the first study to examine the complete set of comment letters for the 2010 and 2017 exposure drafts of government auditing standards.